A Review on Aerospace Materials and Metallurgy - D. Ananth Padmanabhan; T.R. Vijayaram (International Journal of Mechanical Dynamics and Systems Analysis, 2024)
Aerospace metalworking is comparable to the foundation of both space travel and transportation. It involves the scientific design and application of metals and alloys to offer components with the strength required for flight and the ability to survive harsh environments. Although other alloys feature cobalt or iron as the main ingredient, nickel makes up most of alloys used in aeronautical applications. When exceptionally high strength is required in moderate-temperature settings, these alloys are employed. Because properties retain high mechanical qualities across a broad temperature range and are resistant to oxidation and corrosion at high temperatures, stainless steels are utilized in aircraft applications. When "ASM" aerospace requirement metals are needed for any key component, aircraft grade metals—also known as aircraft grade metals or aviation grade metals—are usually utilized. Materials with a high strength-to-weight ratio and generally strong corrosion resistance are required for spaceships, helicopters, especially airplanes. The bulk of parts found in commercial aircraft are made of aluminum alloys. Aluminum is a popular metal for airplanes because of a number of important characteristics, including its non-corrosiveness, light weight, not magnetized and non-sparking nature, and ease of casting and machining. The least popular aluminum alloy in aircraft development is 2024. The alloy is a premium alloy with outstanding endurance to fatigue and a high strain strength. It is frequently utilized in sheet form for the airframe and wings. Despite being heavier, steel has a strength that is up to three times greater than that of aluminum. It usually makes up 11–13% of the materials used in an airplane because of its strength, hardness, and heat resistance, which make it perfect for usage in the landing gear's frame particularly on the aircraft's skin surface. This review article addresses the breadth of metalworking and aeronautical materials. In addition, it describes the many kinds of compounds and their uses in the production of parts for planes. The scope and uses of titanium and aluminum-lithium alloys for the processing of aerospace parts are also covered in this study.
Keywords: ASM; Aerospace metalworking; Aircraft; Ceramic; aluminum-lithium alloys